MARRIAGE IN AGNES GREY BY ANNE BRÃNTE - , LETIZIA AZARINE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Engagement in Victorian era was considered as a way to gain social status than romantic interlude for young men to persuade women in marrying them. Men and women took the engagement seriously as it might lead to beneficial marriage for both parties. This graduating paper analyzes marriage in Victorian era specifically in the novel Agnes Grey by Anne Bronte. The data used for this paper was the story of the novel and quotations related analysis that found. The result shows that marriage in the novel was based on two things: (1) marriage as the beneficial to gain social status, and (2) marriage as the celebration of love. The marriage as the value to gain social status means a woman marries a man from higher status to gain fame and reputation in society. This leads the woman to live in upper class society and increases wealth. The marriage as the celebration of love means the relationship was based on pure love and admiration, which happens to the main protagonist, who disagree with social status view.